Tuberculum Sellae Meningiomas: Outcome of Twenty-eight Cases after Surgery (Bangladesh Journal of Neurosurgery, 2020)
Objective: To present this series of surgically treated tuberculum sellae meningiomas with particular regard to visual compromisesMethods: A retrospective analysis was done on 28 patients (21 females) with meningiomas originating from the tuberculum sellae who underwent surgery between 2010 and 2019. The standard surgical approach of pterional craniotomy. Twelve meningiomas extended posteriorly onto the diaphragma sellae, 13 anteriorly to the planum sphenoidale, and 3 to the anterior clinoid process. 21 tumours involved the optic canal, one bilaterally. Follow up ranged from 6 to 12 months.Results: Total microscopic resection was achieved in 28 patients. Median tumour size was 3.2 cm. Postoperatively, visual acuity improved in 19 patients and deteriorated 3. Preoperative and postoperative visual acuity worsened with increasing duration of preoperative symptoms and with increasing age. Extension into the intraconal space was a negative predictor. Recurrence occurred in one cases. One patients died from causes unrelated to the tumour.Conclusions: In the majority of patients with tuberculum sellae meningiomas, total resection may be achieved through a pterional approach with minimal complications.Bang. J Neurosurgery 2020; 10(1): 39-44